Stress induced changes in hydrogen pressure in contact with tubular diffusion membrane - Kandasamy, K. (Faculty of Science, University of Jaffna, 2015)
Hydrogen permeation studies in Palladium and Palladium alloys reveal that hydrogen diffusion is non-Fickian in metals and their alloys due to the stress field induced by the hydrogen in their lattice. Previously the non-Fickian, uphill diffusion of hydrogen in Pd81Pt19 alloy membrane was explained by attributing it to the modification in the space-time variation of the concentration of dissolved hydrogen in the metal lattice due to Diffusion-Elastic effect. This paper reports evidence for the combined effect on the space-time variation of the concentration of dissolved hydrogen in the lattice by the Gorsky effect and the Diffusion-Elastic effect when hydrogen diffusion initiated in the diffusion membrane either by suddenly increasing or reducing the hydrogen pressure at one wall of the membrane.
Keywords: Diffusion-Elastic effect; Gorsky effect; hydrogen absorption; Joule-Thomson effect; metal- hydrogen system; Non-Fickian Diffusion